Driving Success in the Digital Age: The Role of Emotional Intelligence, Innovation, and Risk-Taking in Culinary MSMEs in South Banjarmasin District, Indonesia - Carroline Vinzentzia Tong; Anisah, Hastin Umi (HM Publisher, 2024)
The rapid growth of digital platforms has transformed the business landscape, presenting both challenges and opportunities for micro, small, and medium enterprises (MSMEs), particularly in the culinary sector. This study investigates the critical factors that drive business success in this dynamic digital age, focusing on the role of emotional intelligence, product innovation, and risk-taking propensity among culinary MSMEs in the South Banjarmasin District, Indonesia. Utilizing a quantitative approach, data were gathered from 40 culinary MSME owners or managers through a structured questionnaire. The research model, grounded in established theoretical frameworks, was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that while emotional intelligence and product innovation exhibit a positive association with business success, their direct impact was not statistically significant in this specific context. In contrast, risk-taking propensity emerged as a powerful predictor of business success, underscoring the importance of calculated risk-taking in navigating the complexities of the digital marketplace. This research contributes valuable insights into the entrepreneurial dynamics of digital-based culinary MSMEs. It highlights the critical role of risk-taking propensity in achieving success, suggesting that a willingness to embrace calculated risks is essential for thriving in the competitive digital landscape. The study also underscores the need for further research to explore the nuanced interplay of emotional intelligence, product innovation, and other factors in driving business success in this sector.